Ressonância Magnética Nuclear e quimiometria como ferramentas de distinção e quantificação de metabólitos de cana-de-açúcar (Saccharum officinarum) e feijão-comum (Phaseolus vulgaris) - ALVES FILHO, Elenilson de Godoy (2010)
Five different common beans cultivars (Phaseolus vulgaris) in the raw conditions, after water immersion (soaking) and after domestic processing (cooking), were studied by NMR in solution and HR-MAS NMR, to obtain a protocol that quantify the oligosaccharides raffinose, stachyose and verbascose contents in bean seeds. The looking for low contents of these oligosaccharides in bean seeds is inserted in Embrapa Arroz e Feijão objectives. This study describes yet the potentiality of chemometric analysis applied in 1H HR-MAS NMR and in solution NMR for investigation of sugarcane varieties. Sugarcane is a primordial material used in Brazil for production of ethanol biofuel. Several technologies to development of new sugarcane cultivars have mainly focused the increase of productivity and greater disease resistance. Sugarcane cultivars are usually identified by organography of leaves and stems, as well as the analysis of peroxydase and esterase isoenzyme activities, soluble total protein and soluble solids content. In this work eight different cultivars of sugarcane leaves were analyzed: RB72454, RB835054, RB835486, RB855113, RB855156, RB855453, RB855536 and RB867515. NMR and chemometric analysis showed useful tools for distinction of the different sugarcane cultivars. In addition, these techniques successfully demonstrated the chemical differences about the investigated cultivars, specially the sugar contents.